1998
DOI: 10.1111/0004-5608.00112
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of Democracy, 1946–1994

Abstract: We examine the relationship between the temporal and spatial aspects of democratic diffusion in the world system since 1946. We find strong and consistent evidence of temporal clustering of democratic and autocratic trends, as well as strong spatial association (or autocorrelation) of democratization. The analysis uses an exploratory data approach in a longitudinal framework to understand global and regional trends in changes in authority structures. Our work reveals discrete changes in regimes that run counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(130 citation statements)
references
References 99 publications
3
121
0
6
Order By: Relevance
“…Similar points have been made by scholars in other contexts (O'Loughlin et al, 1998;Bridge, 2002). Yet, to the best of our knowledge, our study is the first to explore the conditioning role of domestic attributes on extra-territorial influences in the diffusion of organizational standards.…”
Section: Conventional Approaches To Diffusion and Their Shortcomingssupporting
confidence: 87%
“…Similar points have been made by scholars in other contexts (O'Loughlin et al, 1998;Bridge, 2002). Yet, to the best of our knowledge, our study is the first to explore the conditioning role of domestic attributes on extra-territorial influences in the diffusion of organizational standards.…”
Section: Conventional Approaches To Diffusion and Their Shortcomingssupporting
confidence: 87%
“…It is not surprising that democratization on a world scale for these reasons has been found to follow time and space diffusion patterns [18,19,29,36,[43][44][45][46][47][48][49]. As a consequence, one would also expect later adopters to undergo shorter transitions than earlier -though previous studies of that have not been found.…”
Section: Theorymentioning
confidence: 99%
“…In the 860 cases that institutional transitions have occurred, there was a majority with a direction towards increased democracy (511 cases) rather than in the opposite direction (349 cases; binomial test: p b 0.001). Over time, such institutional changes in favor of democracy have resulted in an increasing number of democracies across the globe [19,29,43,44,47,49,60]. Previous analyses of direction and length in institutional leaps also show that transitions tend to cluster in only two major regime-types: autocracy and democracy [14].…”
Section: Transitions/adoption Processesmentioning
confidence: 99%
“…Relative location, in the form of a regional neighbourhood effect, is a second exogenous determinant of political evolution according to the political science literature. For instance, O'Loughlin et al (1998) document global regional fluxes between democratic and autocratic regimes since 1946, which point to a strong regional demonstration effect. They link this to shared contextual constraints: 'At the meso-level [global regional level], certain types of regionally clustered states are more susceptible to democratization than other regions due to "snowballing" or contagion effects from neighbours.…”
Section: Stm and Sanctions Against Anti-social Governancementioning
confidence: 99%